2002
DOI: 10.1103/physrevb.65.245319
|View full text |Cite
|
Sign up to set email alerts
|

Theory of the quantum Hall Smectic Phase. I. Low-energy properties of the quantum Hall smectic fixed point

Abstract: We develop an effective low-energy theory of the quantum Hall ͑QH͒ smectic or stripe phase of a twodimensional electron gas in a large magnetic field in terms of its Goldstone modes and of the charge fluctuations on each stripe. This liquid-crystal phase corresponds to a fixed point that is explicitly demonstrated to be stable against quantum fluctuations at long wavelengths. This fixed-point theory also allows an unambiguous reconstruction of the electron operator. We find that quantum fluctuations are so sev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(77 citation statements)
references
References 43 publications
6
71
0
Order By: Relevance
“…[34,35,36,37,38,39,40]). Recent work on these interesting phases of the two-dimensional electron gas has revealed that magnetic symmetry plays a crucial role in low-energy dynamics of these states.…”
Section: Discussionmentioning
confidence: 99%
“…[34,35,36,37,38,39,40]). Recent work on these interesting phases of the two-dimensional electron gas has revealed that magnetic symmetry plays a crucial role in low-energy dynamics of these states.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][19][20][21] The rise of the smectic phase softens the magnetoroton mode and appears to be responsible for the reduction of the excitation gap for 2.0 < A c < 8.0 as shown in Fig. 1.…”
Section: B Hall-smectic-like Phase In the Intermediate Interaction Amentioning
confidence: 99%
“…In our model we have concentrated on a single string and assumed that rotational invariance has been completely broken, possibly due to a strong orienting field originating from the underlying lattice. A more realistic treatment of smectic and nematic stripe phases in the cuprates should include the interactions between stripes, which are expected to be invariant under small rotations 14 . We defer the study of these issues to the future.…”
Section: Discussionmentioning
confidence: 99%
“…A notable exception is the study of the smectic phase in quantum Hall samples [14][15][16][17][18] . This theory presupposes the existence of a unidirectional charge density wave in the sample and focuses on the quantum mechanical description of the fluctuating chiral edge channels that develop on the boundaries between regions of different filling fraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation